Case Report: Radiotherapy combined with DEB-TACE for hemorrhagic locally advanced solid tumors: a report of 3 cases - Guan, Yunfeng; Shen, Bin (Frontiers in Oncology, 2025)
For patients with certain types of unresectable locally advanced solid tumors, concurrent chemoradiotherapy (CCRT) is the standard treatment regimen. However, in clinical practice, specific patient populations such as the elderly, those with poor performance status (PS) scores, or those with significant underlying comorbidities often struggle to tolerate CCRT, resulting in unfavorable prognosis, and the clinical outcomes are even worse when accompanied by tumor bleeding. This paper reports three specific cases of locally advanced solid tumors (including one case each of lung cancer, esophageal cancer, and cervical cancer) with bleeding that could not tolerate concurrent chemotherapy. All cases received combined treatment of radiotherapy and drug-eluting bead transarterial chemoembolization (DEB-TACE). The results demonstrated that hemorrhagic symptoms were rapidly and effectively controlled in all patients, and all achieved long-term complete response (CR) after treatment. These findings suggest that the combination of radiotherapy and DEB-TACE may be a promising treatment strategy for such specific patients with hemorrhagic locally advanced solid tumors.